Model for student leadership development in student activities: an integrative approach - Pizzano, Denise (My University, 1986)
There exists within the student activities programs and environments, opportunities to enhance student's psychosocial development. Student activities staff have the potential to facilitate this dimension of student development through leadership training programs and structured learning experiences. In spite of these potentials and opportunities, research reveals that little effort is being made to design programs and training experiences to recognize and address these developmental needs of students. This study was conducted to (1) review and critique references dealing with leadership training efforts in student activities, and research studies addressing the potential impact of student activities involvement on student development, (2) design a model for Leadership Development based on a student?s development orientation which determines the overall goals of the program, and provides direction for training, education, and practical experiences, and (3) make recommendation for assessments based on the components of the Leadership Development Model. The model has not been expanded into a readily usable program, nor has it been implemented. As a result, no research has been conducted to evaluate its effectiveness in achieving its stated goals. The model does, however, provide the framework, rationale, and components from which to expand and upon which assessment strategies can be designed.
Keywords: College student development programs; Student activities